DA'WAH IN RESPONDING TO THE PROBLEMS OF CONTEMPORARY RADICALISM - Arifuddin, Arifuddin; Faridah, Faridah (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This research reveals the solution of Da'wah in addressing the problems of contemporary radicalism that works vigilantly and understands further the causes of radicalism that determine the handling of the problems found. There are several causes of radicalism, namely social factors including economic and political factors, religious factors and psychological factors, these three factors equipped with the presence of the internet which causes the problem of radicalism spread more easily in the community. The da'wah solution carried out for the problem of radicalism is the cooperation between all elements of society by implementing actions according to their respective to their main duties and functions. Da'wah is carried out coolly, accompanied by exemplary, Islam must appear in an attractive, friendly, tolerant, moderate form of preaching that is continuously reformed, the practice of the four pillars of nationality (Pancasila, 1945 Constitution, Bhinneka Tunggal Ika, and NKRI). Besides that, there is a need to improve the quality of human resources and equal justice for the entire community.